Ex vivo vaporization performance study of human prostate tissue using in-house designed thulium fiber laser - Krishnendu Maiti; Bikram Haldar; Atasi Pal; Vincent Akash Gomes; Dilip Kumar Pal (Annals of Medical Science and Research)
Introduction: Laser technologies including thulium, Holmium: Yttrium aluminum garnet (Ho: YAG), Potassium-titanyl-phosphate and diode laser have been explored in recent years for the treatment of benign prostatic hyperplasia. These thermal modalities impart their effect through ablative and coagulative mechanisms of action. Although Ho: YAG laser is a gold standard clinical tool in urology, its properties are not sufficient for cutting or coagulation of prostatic tissue. Thulium: YAG laser is a promising alternative laser but with limitations. The recent technological advancements in thulium fiber laser (TFL) provide various advantages along with a compact system for urosurgical applications. This paper depicts the work done in initial validation of an in-house designed TFL in ex vivo vaporization and vaporesection of human prostatic tissue. Comparison of its ablation rate and coagulation zone was done with the existing laser systems. Methods: An in-house designed TFL having maximum continuous wave (CW) power level of 70 W at 1.94 mm optical wavelength had been used for the ex vivo experiment on human prostatic tissue. The rate of tissue vaporization and zone of thermal coagulation were assessed. Results: The in-house made (CSIR-CGCRI, Kolkata, India) CW TFL used at power of 60 W at 1.94 mm was capable of providing tissue vaporization rate of 0.13–0.45 g/min with a thermal coagulation zone of 100 mm. Conclusions: In our study, the TFL was efficient in vaporization, vaporesection, and coagulation of the prostatic tissue under controlled circumstances. Compared to the existing laser systems, the TFL could be a new alternative in Endourology.